Revision of the Ochthebiinae of Venezuela (Coleoptera: Hydraenidae) - Valladares, Luis F.; Short, Andrew Edward Z. (Zootaxa, 2011)
Ochthebiinae Thomson, 1859 is a subfamily of Hydraenidae represented in the Neotropical region by the genera Ochthebius Leach, 1815, Gymnochthebius d’Orchymont, 1943 and Ochtheosus Perkins, 1997 (only in southern South America, Chile). Neotropical Ochthebiinae were mostly revised by Perkins (1980). Also important are the contributions by Balfour-Browne (1971), Anderson (1983), Perkins (1997), Perkins & Archangelsky (2002), Arce-Pérez & Jäch (2004) and Aguilera et al. (2006).